2004
DOI: 10.1103/physrevb.69.245324
|View full text |Cite
|
Sign up to set email alerts
|

Magnetotransport in high-g-factor low-density two-dimensional electron systems confined inIn0.75Ga0.25

Abstract: Magneto-transport in high g-factor, low-density two-dimensional electron systems confined in In We report magneto-transport measurements on high-mobility two-dimensional electron systems (2DESs) confined in In0.75Ga0.25As/In0.75Al0.25As single quantum wells. Several quantum Hall states are observed in a wide range of temperatures and electron densities, the latter controlled by a gate voltage down to values of 1 × 10 11 cm −2 . A tilted-field configuration is used to induce Landau level crossings and magnetic … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
26
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 28 publications
4
26
0
Order By: Relevance
“…The combination of high m and relatively low n is a crucial requirement to study different transport properties when few Landau levels are filled at experimentally accessible magnetic fields [7]. To improve the transport properties of such structures, it is important to understand the scattering mechanisms limiting the low-temperature electron mobility.…”
Section: Article In Pressmentioning
confidence: 99%
“…The combination of high m and relatively low n is a crucial requirement to study different transport properties when few Landau levels are filled at experimentally accessible magnetic fields [7]. To improve the transport properties of such structures, it is important to understand the scattering mechanisms limiting the low-temperature electron mobility.…”
Section: Article In Pressmentioning
confidence: 99%
“…Previous investigations of Zeeman splitting in narrowergap semiconductors have usually led to indications of g-factor enhancement [14][15][16][17][18] although some authors suggest that the effect is small. 19 To date however no systematic studies comparable to the work performed in GaAs and silicon have been reported.…”
mentioning
confidence: 99%
“…In the last few years, the major efforts have been put on InAs and InAs/AlSb 2DEG-based hybrid structures. These materials exhibit a larger g-factor and spin-orbit coupling in comparison to those existing in In 0.75 Ga 0.25 As semiconductor alloys [13][14][15][16] , being therefore more attractive for the implementation of a topological non-trivial phase 1-3 . Moreover, the interplay between spin-orbit coupling and spin-splitting (due to the application of an external magnetic field) may lead to an advanced manipulation and control of the triplet superconducting correlations 17,18 with potential application in spintronics.…”
mentioning
confidence: 99%